Effects of scan body number on digital impression accuracy - Dr Hamidreza Rajatihaghi; Dr Hamidreza Rajatihaghi; Dr Hamidreza Rajatihaghi; Dr Hamidreza Rajatihaghi; Dr Hamidreza Rajatihaghi (Elsevier, 2023)
Aim or Purpose: Impression-making is one of the basic and vital stages in the construction of dental prostheses. To achieve maximum marginal adaptation a precise impression is essential. Impressions for implant treatments require more attention and precision because the characteristics of implants are different from natural teeth. Nowadays, with the introduction of digital systems, digital impression methods have also been introduced. Digital impression-making is receiving much notice today due to the lack of dimensional changes and ease of storage and transfer between the laboratory and the dentist. Considering the importance of impression-making in implant-based treatments, the present study was conducted to investigate the effect of the number of scan bodies on the accuracy of digital impressions. Materials and Methods: An acrylic model of the maxilla, in which eight implants were placed, was used. As a control group, the model was scanned using a laboratory scanner and 8 scan bodies. Then, the model was scanned 10 times with the Freeze method and two scan bodies with the intraoral scanner. In the second group, scanning was done with the conventional method and eight scan bodies. Results: The average error in precision in the Freeze method was 23.76 micrometers and in the conventional method it was 24.36 micrometers. There was no significant difference between the two methods (p=0.803). Conclusions: Both methods of intraoral impression have errors but there was no difference between the two methods in terms of precision and trueness.